Transparency initiatives and Tanzania's extractive industry governance. (1st January 2018) - Poncian, Japhace; Kigodi, Henry Michael
ABSTRACT: The proper management of natural resources and its proceeds is critical for resource-rich countries. Many resource-rich countries have arguably been plagued by aspects of what scholars call 'the resource curse'. Overcoming 'the curse' has thus occupied center stage in studies about extractive resource governance. The Extractive Industries Transparency Initiative (EITI) has been promoted as having the potential to overcome some aspects of the resource curse especially the 'rentier politics'. Several countries have adopted and domesticated the initiative. However, studies on transparency present contradictory findings about the usefulness of the initiative. This paper examines Tanzania's adoption and implementation of transparency in extractive sector governance. The paper examined Tanzania's EITI implementation process, its reconciliation reports and how these reports are used by the parliament, media and civil society to push for governance improvements in the sector. The review of these key documents found that adoption and implementation of the EITI has improved the extractive sector governance by making it more transparent and accountable.